PETROCHEMICAL EMISSIONS PRODUCED BY THE OBJECTS OF THE AUTOMOBILE AND HIGHWAY COMPLEX - Iurchenko, V.; Melnikova, O.; Mykhailova, L.; Fisher, T.; Юрченко, В. А.; Мельникова, О. Г.; Михайлова, Л. С.; Фишер, Т.; Фішер, Т. (Харьковский национальный автомобильно-дорожный университет, 2015)
As a result of experimental researches it was established that the flow of petrochemicals from the objects of the automobile and highway complex that spreads over the adjoining roadside areas correlates with the traffic intensity at objects of the same applicability. The highest specific flow of petrochemicals (per 1 vehicle of traffic) is emitted by gas stations.
ЭМИССИЯ НЕФТЕПРОДУКТОВ ОТ ОБЪЕКТОВ АВТОМОБИЛЬНО-ДОРОЖНОГО КОМПЛЕКСА
ЕМІСІЯ НАФТОПРОДУКТІВ ВІД ОБ’ЄКТІВ АВТОМОБІЛЬНО-ДОРОЖНЬГО КОМПЛЕКСУ
Keywords: objects of automobile-highway complex; environmental safety; emissions; petrochemicals; snow cover; soil; alkanes; PAH; объекты автомобильно-дорожного комплекса; экологическая безопасность; эмиссия; нефтепродукты; снежный покров; почвы; алканы; ПАУ; об’єкти автомобільно-дорожнього комплексу; екологічна безпека; емісія; нафтопродукти; сніжний покрив; ґрунти; алканы; ПАВ; 504:621.317.08